1977
DOI: 10.1364/josa.67.001475
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state evoked potentials

Abstract: The advantages of steady-state EP recording include (1) speed in assessing sensory function in normal and sick infants (e.g., in amblyopia) and in sick adults (e.g., in multiple sclerosis); (2) monitoring certain activities of sensory pathways that do not intrude into conscious perception; (3) rapidly assessing sensory function when a large number of subjects must be tested (e.g., in refraction); (4) objective measurement at very high suprathreshold levels where psychophysical methods are difficult or ineffect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
134
0
7

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(147 citation statements)
references
References 40 publications
3
134
0
7
Order By: Relevance
“…Early human studies using EEG electrodes positioned over occipital cortex (Sperkeijse et al, 1977;Regan, 1977;Tyler et al, 1978;Regan, 1989), and local field potentials recorded within monkey visual cortex (Nakayama and Mackeben, 1982) demonstrated that steady-state responses recorded over visual cortex depend on the temporal frequency of visual input. The dependence of the magnitude of the steady-state response on the input frequency is characterized by local maxima in the response amplitude at the stimulation frequency in at least three different "resonance" bands.…”
Section: Introductionmentioning
confidence: 99%
“…Early human studies using EEG electrodes positioned over occipital cortex (Sperkeijse et al, 1977;Regan, 1977;Tyler et al, 1978;Regan, 1989), and local field potentials recorded within monkey visual cortex (Nakayama and Mackeben, 1982) demonstrated that steady-state responses recorded over visual cortex depend on the temporal frequency of visual input. The dependence of the magnitude of the steady-state response on the input frequency is characterized by local maxima in the response amplitude at the stimulation frequency in at least three different "resonance" bands.…”
Section: Introductionmentioning
confidence: 99%
“…If such speculation can be ccnfirmed, it would mean that the brain contains units which are tuned to this type of stimulation at these particular frequencies. Further, this tuning is specific to stimuli that produce gradual intensity changes, since it is neither found with stroboscopic stimulation nor with alternating checkerboard patterns (Regan, 1977).…”
Section: T Oz O----0mentioning
confidence: 93%
“…It is well established that an occipital lead is appropriate for studying basic functioning of the visual system and for investigating and detecting certain pathological states (Regan, 1977). The expanding range of possible applications for th;is technique raises other questions concerning appropriate sites of electrode placement.…”
mentioning
confidence: 99%
“…Le temps de culmination n'a pas de signification. L'amplitude varie avec la fréquence temporelle de stimulation et présente successivement trois maximums, le premier autour de 10 Hz, puis le deuxième 10% moins ample autour de 18 Hz, enfin le troisième 60% moins ample, autour de 50 Hz (Regan, 1977) (figure V-5-13). Ce résultat correspond probablement à la séparation progressive des vitesses de conduction des signaux le long des différentes voies visuelles -P voie lente et M voie rapide -en relation avec les différents diamètres de leurs axones (Hammett & Smith, 1992), (Milner et al 1972), (Baseler & Sutter, 1997).…”
Section: Pev Flash Stationnairesunclassified